Clinical and molecular fingerprint of SARS-CoV-2 among hospital employees in a period of Omicron BA.2 dominance - Rauschning, Dominic; Weppler, Ruth; Balczun, Carsten; Scheumann, Gwendolyn; Monteiro Marques, Jasmin; Mutschnik, Christina; Preuß, Dominic; Schmithausen, Ricarda Maria; Starke, Maximilian; Hagen, Ralf Matthias; Döhla, Manuel (GMS Hygiene and Infection Control)
In the spring of 2022, SARS-CoV-2 Omicron BA.2 peaked in Germany. The main burden was staff shortage. To achieve effective identification and management of infected persons as well as early reintegration of recovered persons, an infection-control outpatient clinic was established at the Bundeswehr Central Hospital Koblenz. This article reports a secondary data analysis of 663 people with 1,174 visits to the outpatient clinic. For asymptomatic contacts, no correlation was observed between PCR result and testing time or frequency. Although no significant symptoms were documented, a high correlation was found between a positive antigen self-test and positive PCR. For clearance, a median time until a negative test was obtained was 8–11 days. The PCR gold standard was compared with ECLIA antigen testing for all indications. The results of this study challenge the rationale for testing asymptomatic contacts. Solely symptom-driven diagnostics by PCR also do not seem to be effective. However, contact persons or symptomatic persons with a positive rapid antigen test should be tested further. Whether this testing is done by ECLIA or PCR does not seem to matter. Clearance testing after recovery prior to day 8 is also not appropriate.